Description of the process of developing a rubric specific to a learning and evaluation situation in the context of modifying learning content for secondary school students with autism spectrum disorder - Marie-Aimée Lamarche; Micheline-Joanne Durand (ADMEE-Canada, 2022)
The development of rubrics is a complex task that requires a good knowledge of the object of evaluation and the learning level of the students for whom it is intended. From the several types of rubrics used in school environments, the analytic rubrics and developmental rubrics prove to be especially appropriate choices to guide the judgment of the evaluators. By following the research and development methodology, the designers engaged in a reflective process which, after many round trips in the formulation of criteria, scale and descriptors, led to the development, validation and implementation testing of three prototypes of analytic rubrics. The results make it possible to identify the elements to be considered in the construction of this tool for pupils with autism spectrum disorder (ASD) in the first cycle of secondary school who present a great diversity of cognitive profiles.